Experimental study on thermal performance of air-PCM unit to be used for limited time air conditioning of military land vehicles - Ozaydin, Halil Can; Atayilmaz, S. Ozgur (ELSEVIER, 2024)
In this study, the thermal performance of an air-phase change material (PCM) unit, developed to support the air conditioning of military land vehicles during limited time engine-off operations, has been experimentally investigated. In the experimental studies, the effects of air inlet temperature, air flow rate and PCM phase change temperature on the thermal performance of the air-PCM unit in discharge phase have been studied. In this study, paraffin-based pure RT10HC and RT21HC phase change materials, encapsulated in 450 x 300 x 15 mm cases have been used. Experimental studies have been carried out at constant air inlet temperatures of 32 degrees C, 36 degrees C and 40 degrees C, and constant air flow rates of 125 m3/h, 250 m3/h and 375 m3/h. The effects of the test parameters on heat transfer, air outlet temperature, air conditioning duration, PCM melting time and thermal efficiency of the system have been analyzed. It has been observed that while the air flow rate has been decreasing, the air conditioning duration has increased and the blowing temperature has decreased. In particular, for the temporary engine-off operations, low air flow rates have been found to be advantageous over high air flow rates in the same conditions due to both providing longer air conditioning time and higher thermal efficiency. The results suggest that there are many experimental conditions in which blowing temperatures of 30 degrees C and below have been achieved for the 30-min transient engine-off operation period within the scope of this study. Results have confirmed that the analytical model developed within the scope of the study is consistent with the experimental studies within f9 % deviation. The results are promising in the field of free-cooling applications involving airPCM units developed for military land vehicles.
Keywords: Thermal energy storage; Phase change material (PCM); Free cooling; Air-PCM heat exchangers; Latent heat storage; Military vehicle air conditioning; PHASE-CHANGE MATERIAL; ENERGY-STORAGE; HEAT-EXCHANGER; EXPERIMENTAL VALIDATION; COLD-STORAGE; SYSTEM; SIMULATION; MANAGEMENT; Energy & Fuels